IMPLEMENTASI PENDIDIKAN KARAKTER DI SEKOLAH DASAR: Upaya Pendidik Membentuk Karakter Siswa Dalam Mempersiapkan Generasi Emas 2045 Berbasis Neurosains - Dini Nurul Insani; Chasan Arif; Dede Indra Setiabudi (Student Scientific Creativity Journal, 2023)
Education is a creative endeavor and an absolute necessity for human beings. character. This cannot be separated from the role of parents and teachers. parent first Teacher, character development is not only during childbirth, but during pregnancy uterus. Moreover, teachers, especially in primary schools, have the same obligations. in character building. In doing so, teachers must use brain-based characters Educational Approach (Neuroscience). The reason is the success of character building Start by changing the brains of your students. When brain-based character building is applied From an early age, Indonesian education is of higher quality, We can prepare high quality Golden Generation 2045. This survey uses qualitative research Based on a literature survey. Based on the results of research, this quality was established Education is an education that can shape the character of a student. Character Education is changing, so using a brain (neuroscience) approach is more effective Characters start by changing the brains of students.